Response to the Letter to the Editor: "Mitochondria isolated from the striatum of the brain exhibit a higher degree of oxidative phosphorylation coupling, which shows that they are not subject to energetic dysfunction upon acute paraquat administration" - Czerniczyniec, Analia (2016)
In his Letter to the Editor, Professor Rendon states that our published work entitled “Impairment of striatal mitochondrial function by acute paraquat poisoning”, published in J Bioenerg Biomembr 2015; 47(5): 395–408, a part of the methodology used and the interpretation of the results exhibit serious fallacies and contradictions that do not support the stated conclusions with respect to the negative alterations of the bioenergetics observed in the striatum mitochondria after paraquat treatment.